Design System of Student Registration and The Purchase of Musical Concert Ticket at Samuel Riedone Course & Music Performance - Peryo Suliantino; Andi Leo (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2020)
Music is an entertainment media for most people in the world. The existence of music can help all work activities done by people. In the world of music itself there are also various musical instruments that create a beautiful blend of sound and calm the mind. Instruments that are very influential and can make the feeling of a person feeling happy and happy among them is piano. A well-known private piano course in BSD area called Samuel Riedone private Piano course, Prepare a range of learning materials and a highly skilled and enjoyable teaching team. But the name of the music course also has bureaucracy or administration that must be run every day so that the running business process can be as expected. To facilitate the manual business process is now more modern it will be created a WEB-based information system that is able to assist in the daily business process. The system will use the Term Frequency (TF) and Inverse Document Frequency (IDF) methods to be able to process the data of many documents in the business process from the music course., And by using the PHP programming language and MySQL database to create the system.